Chemical Cocktail Induces Hematopoietic Reprogramming and Expands Hematopoietic Stem/Progenitor Cells. Issue 1 (11th November 2019) - Zhou, Yi; Zhu, Xingli; Dai, Yuting; Xiong, Shumin; Wei, Chuijin; Yu, Pei; Tang, Yuewen; Wu, Liang; Li, Jianfeng; Liu, Dan; Wang, Yanlin; Chen, Zhu; et al.
Abstract: Generation of hematopoietic stem/progenitor cells (HSPCs) via cell expansion or cell reprogramming has been widely achieved by overexpression of transcription factors. Herein, it is reported that without introducing exogenous genes, mouse fibroblasts can be reprogrammed into hemogenic cells based on lineage tracing analysis, which further develop into hematopoietic cells, by treatment of cocktails of chemical compounds. The chemical cocktails also reprogram differentiated hematopoietic cells back into HSPC‐like cells. Most importantly, the chemical cocktails enabling hematopoietic reprogramming robustly promote HSPC proliferation ex vivo. The expanded HSPCs acquire enhanced capacity of hematopoietic reconstruction in vivo. Single‐cell sequencing analysis verifies the expansion of HSPCs and the cell reprogramming toward potential generation of HSPCs at the same time by the chemical cocktail treatment. Thus, the proof‐of‐concept findings not only demonstrate that hematopoietic reprogramming can be achieved by chemical compounds but also provide a promising strategy for acquisition of HSPCs by chemical cocktail‐enabled double effects. Abstract : A chemical cocktail is used to convert differentiated hematopoietic cells into hematopoietic stem/progenitor cell (HSPC)‐like cells. The cocktail can also robustly promote HSPC expansion ex vivo. This study is the proof‐of‐concept that hematopoietic reprogramming can be induced only by chemical compounds without introduction of exogenous genes, and generation of HSPCs can be achieved simultaneously via two diverse directions: expansion and reprogramming.